What moral weight should patient-led demand have in clinical decisions about assisted reproductive technologies? - Stanbury, Craig (Bioethics, 2024)
Evidence suggests that one reason doctors provide certain interventions in assisted reproductive technologies (ART) is because of patient demand. This is particularly the case when it comes to unproven interventions such as ‘add-ons’ to in vitro fertilisation (IVF) cycles, or providing IVF cycles that are highly unlikely to succeed. Doctors tend to accede to demands for such interventions because patients are willing to do and pay ‘whatever it takes’ to have a baby. However, there is uncertainty as to what moral weight should be placed on patient-led demands in ART, including whether it is acceptable for such demands to be invoked as a justification for intervention. We address this issue in this paper. We start by elucidating what we mean by ‘patient-led demand’ and synthesise some of the evidence for this phenomenon. We then argue that a doctor's professional role morality (PRM) yields special responsibilities, particularly in commercialised healthcare settings such as ART, because of the nature of professions as social institutions that are distinct from markets. We argue on this basis that, while there may be reasons (consistent with PRM) for doctors to accede to patient demand, this is not always the case. There is often a gap in justification between acceding to patient-led demands and providing contested interventions, particularly in commercial settings. As a result, acceding to demand in such settings needs a strong justification to be consistent with PRM.